An introduction to digitalizing work in the Nordics - Komp-Leukkunen, Kathrin; Poli, Arianna (Nordic Journal of Working Life Studies, 2024)
Digital technologies have become an essential part of our everyday lives. While they were still a curious novelty in the 1960s and 1970s, they seem to permeate an ever- increasing part of today’s societies (Levin & Mamlok 2021). By now, they are no longer confined to offices, where people need to physically sit in front of computers to use them. Instead, they are ubiquitous, with handheld devices being portable, and wearable technologies frequently even unobtrusive (Delabrida Silva et al. 2018). Augmented Realities blur the lines between technology and reality, while Virtual Realities even place a technological layer over our realities (Arena et al. 2022). Our technologically embedded lives create a myriad of data, which is used for various kinds of communication and as a currency. It is shared on social media for social interaction and to cultivate a personal image (Hall 2018). Moreover, it is routinely shared with companies for marketing and product development, sometimes in exchange for services (Cao et al. 2022). Thus, the datafication of our lives pulls us into a complex network of interactions (...)